Addendum eleoscopico, palmonantico e metopomantico ("Athous Iviron 4301, Atheniensis EBE" 1350 e 1275) - Costanza, Salvatore (Byzantion, 2018)
It is worth drawing attention to new manuscript evidence for the history of Byzantine and Modern Greek divination. Firstly, new testimonies - viz. Athous Iviron 4301 and Atheniensis EBE 1350 - of the versio A of the De naevis, previously known only by Peruschi’s first edition (Rome, Blado, 1545), are given. The material concerns elaeoscopy, that is, divination by moles, which were believed to be prophetic signs - in fact, a kind of Physiognomic. The textus receptus of the treatises On moles is emended (see § 5 b, 26 a) and critically established. Secondly, the article deals with short treatises from Atheniensis EBE 1275 concerning physiognomic methods applied to palmomancy, that is, divination by twitching of the hands, and to metopomancy, that is, prophecies drawn from the lines in the forehead. This shows how popular these kind of prophecy were in post-Byzantine times.